Language, persuasion and passions - Cárdenas Mejía, Luz Gloria (Estudios de Filosofía, 2006)
Contemporarily, Austin, based on his theories of the acts of speech, established that persuasion It a "perlocutionory" act, if ts an effect, among others, produced by a speaker on another by means of a speech. Aristotle defined Rethorfc as the faculty of considering in each case what is useful to persuade. As the first part of our work points out, persuasion, for Aristotle, is produced through discourse. If this is so, and if passions are also necessary for its production, they must be able to be expressed using language with the intention of demonstrating this, we proceed in the following manner: first, the connection between Persuasion and Opinion, as well as the connection between these with Words, will be dealt with. Second, given the connection aprecision is made that fathermore than the fact that man communicates, something that animals do as well, he also expresses himself through language. And wt will finally make the fallowing consideration.' if by means of the passions changes take place not only in thebody but are felt by the soul, man could also build enunciations that refer to them.